Tongue imaging during drug-induced sleep ultrasound in obstructive sleep apnea patients. Issue 5 (October 2020) - Abuan, Michael Ryan A; Lin, Wan-Ni; Hsin, Li-Jen; Lee, Li-Ang; Fang, Tuan-Jen; Chen, Ning-Hung; Lo, Yu-Lun; Li, Hsueh-Yu
Abstract: Objectives: The aims of this study are to examine the changes of tongue thickness and distance of two lingual arteries through drug-induced sleep ultrasound, and explore the relationship between sonographic measurements and clinical data. Materials and Methods: A total of 26 confirmed obstructive sleep apnea patients were recruited in this one-year study. All patients received ultrasound examination twice (wakefulness and drug-induced sleep) in sleep center under level 1 polysomnographic monitor. Drug-induced sleep was performed by administration of one Stilnox (Zolpidem, 2 mg/tablet) and ultrasound procedure commenced once stage 2 sleep shown in polysomnography. Ultrasound imaging was implemented via submental approach with transducer position at the sagittal midline of the submental area (sagittal view) to measure thickness of the tongue. Transducer was then moved at a transverse midpoint between the inferior border of the mandible and the hyoid bone (transverse view) to measure the distance between 2 lingual arteries. Results: The distance between 2 lingual arteries elongated significantly ( p  < .001) and thickness of tongue muscle became thinner during drug-induced sleep. The distance between 2 lingual arteries (sleep) had positive correlation with apnea/hypopnea index (AHI, r  = 0.51, p  = .008) and body mass index (BMI, r  = 0.46, p  = .018). Conclusion: Drug-induced sleep ultrasound is feasible to measure changes of tongue in OSA patients. Ultrasound imaging showed that tongue muscle became thinner in conjunction with significant widening in distance between two lingual arteries during hypnotic-induced sleep and that was positively correlated with AHI and BMI. Drug-induced sleep ultrasound may be helpful to enhance safety in tongue surgery for OSA patients.